2008
DOI: 10.1002/adem.200700184
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Limits in Shape‐Memory Polymers

Abstract: Shape-memory polymers are mechanically active materials designed to store a temporary deformed shape and subsequently recover a pre-programmed permanent shape upon exposure to external stimuli such as temperature or light. [1][2][3] The capacity of shape-memory polymers to transition between different physical shapes has led to a myriad of proposed minimally invasive biomedical applications [4] including sutures, [5] vascular stenting and repair, [6][7][8][9][10] stroketreating devices, [11,12] and microfluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
88
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 31 publications
12
88
0
Order By: Relevance
“…The failure strain of our 15 mol% PETMP system was maximized when strained near T g , as measured by the peak of tan ∂. This is also in good agreement with previous studies that demonstrated the maximum strain in amorphous SMP networks occurred between the onset of the glass transition and T g ; 35,36 however, the LCE samples did not experience a rapid decrease in failure strain when heated above T g , as shown in most elastomers. 37 This can be attributed to the elevated tan ∂ region that exists between T g and T i (i.e., the nematic phase).…”
Section: Discussionsupporting
confidence: 78%
“…The failure strain of our 15 mol% PETMP system was maximized when strained near T g , as measured by the peak of tan ∂. This is also in good agreement with previous studies that demonstrated the maximum strain in amorphous SMP networks occurred between the onset of the glass transition and T g ; 35,36 however, the LCE samples did not experience a rapid decrease in failure strain when heated above T g , as shown in most elastomers. 37 This can be attributed to the elevated tan ∂ region that exists between T g and T i (i.e., the nematic phase).…”
Section: Discussionsupporting
confidence: 78%
“…The samples were prepared in the same way as for their mechanical characterization (see Figure 2). The experiments were performed following the steps shown in Figure 4 three Tprog were chosen: Tg E′ , Tg and Tg + 20, to quantify the SMR at the optimal mechanical point (Tg E′ ) [9,10] and along the glass transition process (Tg and Tg + 20). The samples were heated up to Tprog and held during 5 min at this temperature to ensure thermal equilibrium (point 1 in Figure 4).…”
Section: Quantitative Studymentioning
confidence: 99%
“…The results indicated that by carefully varying the network structure it was possible to increase the tensile elongation while maintaining high values of glass transition temperature (T g ) and obtaining excellent shape-recovery performances. On the other hand, another approach to enhance the ultimate strain based on the effect of the programming temperature (T prog ) was investigated by Yakacki et al [9] working with acrylates and Rousseau et al [10] using epoxy-based systems. The results demonstrated an improvement of the strain at break of three-to five-fold, when deforming at a temperature slightly below the T g , corresponding to the onset point of the network relaxation process (measured by dynamic-mechanical analyses).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison purposes, the shape-recov-366 ery ratios, R r , of the shape-memory experiments 367 carried out at the corresponding programming tem-368 peratures and up to e D = 75 % are also shown in 369 Table 3. 370 First of all, as explained in our previous work [14], 371 the optimal mechanical point was found at T g E ', in 372 which both the stress and strain at break values were 373 enhanced, a physical effect called viscoelastic tough-374 ening [34,35]. Moreover, the values obtained are 375 higher than those reported by other authors with 376 epoxy-based systems, especially for the stress at 377 break (up to 55 MPa on the 3thiol-NEAT formulation 378 with 95 % of e b at T g E' ) [ 36,37].…”
mentioning
confidence: 99%